Co-liquefaction of swine manure with waste vegetable oil for enhanced bio-oil production. Issue 4 (16th February 2016) - Xiu, Shuangning; Shahbazi, Abolghasem; Wang, Lijun
ABSTRACT: Waste vegetable oil was co-liquefied with swine manure to determine the bio-oil potential in this study. The result shows that co-liquefaction of waste vegetable oil with swine manure can improve the bio-oil production and decarboxylation of waste vegetable oil. The weight ratio of swine manure to waste vegetable oil exerted a great effect on both the yield and quality of the bio-oil. The optimum weight ratio of swine manure to waste cooking oil was 1:3, where a maximum oil yield of 80% was obtained with higher calorific value up to 38 MJ/kg.